Representations of ambiguity in selected writings by women from Guadeloupe and Martinique - Brennan, Daria Mary (Trinity College (Dublin, Ireland). Department of French, 2003)
This thesis looks at selected writings of women from Martinique and Guadeloupe through the complex theme of ambiguity. The novels and short stories of authors such as Mayotte Capécia, Myriam Warner-Vieyra and Maryse Condé are presented in terms of their representation of a certain type of ambiguity that is revealed either through the use of opposition or of a specific context. In chapter one the source of ambiguity lies in the treatment of space in the memoirs of a Martinican Békée Élodie Dujon-Jourdain, and the Guadeloupean writer Maryse Condé's novel Traversée de la mangrove. In both of these texts space is used as a designated site of otherness and as a metaphor of constraint. Chapter two looks at the model of the métisse as it is treated in Mayotte Capécia's novel Je suis Martiniquaise, Michele Lacrosil's novel Cajon, and Franciane Galou's short story 'Une simple question de couleur'.
Keywords: French Language and Literature, Ph.D.; Ph.D. Trinity College Dublin